Priorities of Russian Energy Policy in Russian-Chinese Relations - Meynkhard, Artur (International Journal of Energy Economics and Policy, 2019)
The priorities of Russian energy policy on the basis of Russian energy strategy until 2035 are proposed. Having narrowed the changes in Russia’s energy policy, the article notes that the main priorities are strengthening the participation of China Development Bank in energy deals, building LNG and Pipelines in the context of energy cooperation, increasing the trust in Russia-China energy relations. The main limiting factor is not so much the limited resources as the costs of fuel production and the possibility of increasing the volume of energy exports to China, as well as low levels of energy efficiency and energy saving. In this situation, the possibility of progressive development of relations between China and Russia can be achieved only through fundamental changes in the industry. Expanding the field of cooperation energy investments is worth mentioning. Keywords: Alternative Energy Sources, Energy Policy, Resource Saving, Energy Efficient Development, Energy Indicators. JEL Classifications: C30, D12, Q41, Q48 DOI: https://doi.org/10.32479/ijeep.8507